Assessing the role of public relations in improving beneficiary participation in Kumasi Metropolitan Assembly’s activities. - Pipim, Nana Kwadwo (KNUST, 2025)
Thesis Submitted In Partial Fulfilment Of The Requirements For The Degree Of Master Of Public Administration.